2018
DOI: 10.1016/j.jiph.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E in Italy: A silent presence

Abstract: Hepatitis E virus (HEV) was discovered in the 1980s and has been considered as being confined to developing countries. The purpose of this critical review was to determine the reported HEV seroprevalence rates in Italy, to identify predisposing factors and individuals at risk and to assess possible importation of HEV by immigrants. A critical review of 159 articles published in PubMed from 1994 to date was done. Only 27 original reports of 50 or more subjects, written in the English or Italian language, were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 85 publications
1
16
0
Order By: Relevance
“…In spite of this, our data confirm the enhanced diffusion of HEV and HAV in MSM, previously described in Rome and contribute to outlining the HEV epidemiology in Italy in this population …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In spite of this, our data confirm the enhanced diffusion of HEV and HAV in MSM, previously described in Rome and contribute to outlining the HEV epidemiology in Italy in this population …”
Section: Discussionsupporting
confidence: 89%
“…In Italian general population the seroprevalence range from 0.12% to 49% with the highest rate in the central region. In particular in Northern Italy the rate is from 1.3% to 9%, while in central‐south Italy from 1.3% to 49 % …”
Section: Discussionmentioning
confidence: 97%
“…Of the 28 EU member states, 8 countries have implemented HEV-RNA donor screening (Table 2; November 2012 to April 2018) [16-23]. Six of the remaining 20 EU countries have published blood donor data.…”
Section: Overview Of Eu Blood Donor Screening Methods and Strategiesmentioning
confidence: 99%
“…Others studies showed that this efficiency in GWR method is better than the OLS method. For example, the correlation between some factors and notifications of Dengue in Pakistan was 0.37 in OLS model and 0.49 in GWR model 13 . An aspect to consider is that these correlations can vary in space and time.…”
Section: Discussionmentioning
confidence: 99%